Case Report: Diagnostic assessment, developmental trajectory and treatment approaches in a case of a complex neurodevelopmental syndrome associated with non- synonymous variants in MECP2 (p. R133C) and GABBR1 - Napoli, V.; Guerrera, S.; Demaria, F.; Piccolo, G.; Cianfa, A.; Passarini, S.; Logrieco, M. G.; Zanni, G.; Valeri, G.; Vicari, S. (Frontiers in Pediatrics, 2025)
BackgroundRett Syndrome (RTT) is an X-linked progressive disease affecting 1 in 10,000 females. MECP2 p.R133C, is the second most common variant affecting more than 4% of all RTT cases. GABBR1 pathogenic variants have been recently associated with mild to severe psychomotor delay, epilepsy, intellectual disability (ID), autism (ASD), attention deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD).Material and methodsWe report a 13.9-year-old girl, with a complex neurodevelopmental disorder including ASD, ID with the appearance, at 9 years of age, of vocal and motor tics involving the upper limbs and trunk, suggesting a diagnosis of Tourette's syndrome (TS). Tics were also present in the mother and grandmother. The patient was followed-up for approximately 10 years and underwent periodic clinical and neuropsychological evaluations. We performed Trio-based WES analysis and segregation analysis in relevant family members.ResultsA de novo MECP2 variant (p. R133C) was detected in the proband. Moreover, a maternally inherited VoUS class 3 in GABBR1 (p. F692S), was identified in the proband, and segregated in the mother and grandmother. No functional studies confirm the pathogenicity of this GABBR1 variant, and Tourette phenotypes have not been previously linked to GABBR1. Based on familial segregation, we hypothesize that this variant may worsen the MECP2-related phenotype and underlie the Tourette symptoms seen in all carriers. Tourette phenotypes have never been reported with MECP2 variants alone. Although Rett-like features are mainly due to MECP2 loss-of-function, MECP2 deficiency disrupts GABAergic signaling, making GABA modulators potential therapeutic targets. The presence of the GABBR1 variant may further impair GABA receptor neurotransmission. Thus, the GABBR1 variant may be a modifying factor in this case, though its pathogenicity remains uncertain. Despite attempts to manage her condition with appropriate pharmacological therapies, progressive muscle hypertonia and behavioral issues, persisted. The patient showed improvements in engagement and emotional regulation, during music therapy sessions.ConclusionWe describe the developmental trajectory of an adolescent with overlapping features of Rett and Tourette syndromes, carrying MECP2 and GABBR1 variants. Future studies are essential to better characterize the genotype-phenotype correlates and optimize therapeutic strategies, to tackle the unique needs of the patient and her family.